Graphene‐Mimicking 2D Porous Co3O4 Nanofoils for Lithium Battery Applications. (14th September 2016) - Eom, Wonsik; Kim, Ayoung; Park, Hun; Kim, Hansu; Han, Tae Hee
Abstract : 2D nanoscale oxides have attracted a large amount of research interest due to their unique properties. Here, a facile synthetic approach to prepare graphene‐mimicking, porous 2D Co3 O4 nanofoils using graphene oxide (GO) as a sacrificial template is reported. The thermal instability of graphene, as well as the catalytic ability of Co3 O4 particles to degrade carbon backbones, allow the fabrication of porous 2D Co3 O4 nanofoils without the loss of the 2D nature of GO. Based on these results, a graphene mimicking as a route for large‐area 2D transition metal oxides for applications in electrochemical energy storage devices is proposed. As a proof of concept, it is demonstrated that graphene‐like, porous 2D Co3 O4 nanofoils exhibit a high reversible capacity (1279.2 mAh g −1 ), even after 50 cycles. This capacity is far beyond the theoretical capacity of Co3 O4 based on the conversion mechanism from Co3 O4 to Li2 O and metallic Co. Abstract : 2D porous Co3 O4 nanofoils without the loss of 2D nature of graphene oxide (GO) are prepared by using GO as a sacrificial template. By taking advantage of the catalytic ability of Co3 O4 to degrade carbon backbones, as well as the thermal instability of graphene, porous 2D Co3 O4 nanofoils consisting of Co3 O4 nanocrystals (about 10–20 nm in diameter) are successfully synthesized and exhibit a high reversible capacity of 1279.0 mAh g −1 even after 50 cycles.